2012
DOI: 10.1111/j.1365-2109.2012.03175.x
|View full text |Cite
|
Sign up to set email alerts
|

Family growth response to different laboratory culture environments shows genotype-environment interaction in the sea urchin Strongylocentrotus intermedius

Abstract: This study investigated the genetic variation and genotype-environment interaction (GEI) in the early growth stage among seven full-sib families of the sea urchin Strongylocentrotus intermedius. From each of the seven families, 180 or 270 sea urchins of the same size were exposed to three laboratory environments (E 1 , E 2 and E 3 ). These environments were commonly used in breeding programs for S. intermedius. After a 102 days trial, test height, test diameter, body weight and the coefficient of variation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 26 publications
(48 reference statements)
3
17
3
Order By: Relevance
“…Family did not significantly affect the growth traits during P1, but did significantly affect growth traits during the other three periods (results by GLM analysis). This differed from previous studies [19], where it was reported that family had a significant effect on the growth of S. intermedius during early growth stages (six months old to 10 months old). One potential reason for this difference is that sea urchins selected by Zhang et al [19] were similar in size whereas.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Family did not significantly affect the growth traits during P1, but did significantly affect growth traits during the other three periods (results by GLM analysis). This differed from previous studies [19], where it was reported that family had a significant effect on the growth of S. intermedius during early growth stages (six months old to 10 months old). One potential reason for this difference is that sea urchins selected by Zhang et al [19] were similar in size whereas.…”
Section: Discussioncontrasting
confidence: 99%
“…At harvest, the proportion of variance explained by family for BW had reached 20.686%. Zhang et al estimated the proportion of variance explained by family for TD and BW as 0.465%–0.944% [19]. These results were much lower than our results.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…(2002) studies. However, recent studies indicate that differences in intrinsic growth rates in this study may be attributed to genetic variability (Liu et al ., 2003, 2005; Zhang et al ., 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Extrinsic factors affecting growth include availability and nutrient content, bioavailability of nutrients (Lawrence & Lane, 1982), habitat (Ebert, 1968; Agatsuma, 2007; Andrew & Byrne, 2007), population density (Siikavuopio et al ., 2007; Richardson et al ., 2011), competition (Grosjean et al ., 1996), osmotic condition (Giese & Farmanfarmaian, 1963), and temperature (Moore et al ., 1963; Agatsuma, 2007). Intraspecific variability in sea urchin growth rates may also be related to genetic variation, genomic expression, or epigenetic influences, some of which have been described in sea urchins (Liu et al ., 2003, 2005; Zhang et al ., 2012). …”
Section: Introductionmentioning
confidence: 99%